Pemahaman Fungsi Manajemen SDM dan Dampakya pada Kinerja - Muhammad Aidin; Zafitri Nur Vadilla; Mawar Nur Indah Sari; Adam Andae (Jurnal Simki Economic, 2026)
This study aims to analyze the effect of understanding the Human Resource Management (HRM) function on performance. The study uses a quantitative approach with a survey method by distributing questionnaires to final year students and recent graduates who have work or internship experience. The sampling technique used is purposive sampling. Data were analyzed using validity tests, reliability tests, and simple linear regression with the help of SPSS. The results of the regression analysis indicate that understanding the HRM function has a positive effect on performance with a regression coefficient of 0.567. The t-test shows a calculated t-value of 6.914 with a significance level of 0.000 (<0.05), so the hypothesis stating that there is a positive and significant effect between understanding the HRM function on performance can be accepted. The coefficient of determination of 0.321 indicates that understanding the HRM function contributes 32.1% to performance.